PEREMPUAN BERTATTOO DI KOTA PEKANBARU - Nancy Saudia; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the city of Pekanbaru. The purpose of this study was to determine whether the reason for women to wear a tattoo and whether the meaning of the tattoo for a tattoo receipts women in the city of Pekanbaru. This study, entitled "Women tattooed In Pekanbaru City Riau Province". Topics focus of this study is whether the reason women wear a tattoo in the town of Pekanbaru. informants of this study were women bertattoo in Pekanbaru. Sampling was done by accidental sampling technique. Samples are numbered 5 women tattooed. The author uses qualitative descriptive method and data analyzed qualitative. Data instrument is observation, interview and documentation. The results showed that the reason women using a tattoo on the body is due to the bandwagon, immortalize special moments, seek attention, accecories, and friendship. In addition the results of the research field known tattoo meaning for women users in Pekanbaru tattoo is an expression of feelings, art and beauty, identity, and emotional outlet.Keywords: Women tattooed, meaning Tattoo, Feminism